2013
DOI: 10.4161/epi.26597
|View full text |Cite
|
Sign up to set email alerts
|

Enhancer transcribed RNAs arise from hypomethylated, Tet-occupied genomic regions

Abstract: Enhancers are cis-acting elements capable of regulating transcription in a distance and orientation-independent manner. A subset of enhancers are occupied by RNA polymerase II (RNAP II) and transcribed to produce long non-coding RNAs termed eRNAs. We thoroughly investigated the association between eRNA productivity and various chromatin marks and transcriptional regulators in mouse embryonic stem cells (ESCs) through an integrative approach. We found that eRNA-producing enhancers exhibited elevated levels of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
92
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2
1

Relationship

4
6

Authors

Journals

citations
Cited by 62 publications
(96 citation statements)
references
References 58 publications
3
92
0
1
Order By: Relevance
“…Despite the correlation of these histone marks with enhancer transcription, Zhu et al found that eRNA was the single most predictive indicator of enhancer activity, with eRNA synthesis being more signifi cantly associated with increased expression at nearby genes than histone marks in multiple cell types. These results are supported by a separate study by Pulakanti et al where it was found that eRNA synthesis correlated with H3K27Ac deposition, hypomethylation, and occupancy of the DNA hydroxylase Tet1 in embryonic stem cells, all of which are traditional markers for transcriptional activity (Pulakanti et al 2013 ).…”
Section: Enhancer Transcription As a Marker Of Activitysupporting
confidence: 77%
“…Despite the correlation of these histone marks with enhancer transcription, Zhu et al found that eRNA was the single most predictive indicator of enhancer activity, with eRNA synthesis being more signifi cantly associated with increased expression at nearby genes than histone marks in multiple cell types. These results are supported by a separate study by Pulakanti et al where it was found that eRNA synthesis correlated with H3K27Ac deposition, hypomethylation, and occupancy of the DNA hydroxylase Tet1 in embryonic stem cells, all of which are traditional markers for transcriptional activity (Pulakanti et al 2013 ).…”
Section: Enhancer Transcription As a Marker Of Activitysupporting
confidence: 77%
“…Reads were aligned to mm9 by using the command line (-e 70 -k 1 -m 1 -n 2 -best -concise) on the software BowTie. Peaks were then identified by using MACS (model-based analysis of ChIP-seq) (66), using a two-sided comparison with input DNA when available, with default parameters (27).…”
Section: Quantitative Reverse Transcription-pcr (Rt-pcr)mentioning
confidence: 99%
“…We found an increase of 5-hydroxy-methyl-CpG (Fig. 6C), which was recently suggested to take part in the function of activated enhancers (40). In addition, by performing ChIP analysis, we observed slight increases of histone H3K4m3 (Fig.…”
Section: Resultsmentioning
confidence: 67%